2019
DOI: 10.23939/chcht13.02.218
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Heat-and-Power Plants Water Purification

Abstract: The effect of the content of natural and anthropogenic pollutants (potentially acidic organic substances, synthetic surfactants and petroleum products in water, which is exposed to desalting) on the efficiency of КU-2-8 ion exchangers has been studied. To minimize this negative influence the reagent method was used. Different natural and modified sorbents have been investigated for additional purification of water before filtration on cation-exchange filters or periodic regeneration of ion exchangers by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In the study, the estimation of possibilities of application of geoinformation systems for estimation of potential of renewable energy sources in Ukraine is executed with use of methodological bases and scientific results from a number of previous studies [16][17][18][19][20][21][22], and also using databases and interactive resource maps on global renewable energy sources from the internet [23][24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…In the study, the estimation of possibilities of application of geoinformation systems for estimation of potential of renewable energy sources in Ukraine is executed with use of methodological bases and scientific results from a number of previous studies [16][17][18][19][20][21][22], and also using databases and interactive resource maps on global renewable energy sources from the internet [23][24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…Their content in water when supplied to the population differs lit t le from the content in natural waters near the water intake, and in some cases even becomes greater. Studies of drinking water and changes in the content of metals at various stages of water treatment have shown that the water is not purified from heavy metals, but their concentrations (in particular, Fe and Mn) are increasing due to leaching from pipelines in the process of water supply [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for the deterioration of the ecological condition of surface water bodies are insufficient number and low level of efficiency of existing treatment facilities, limited number of return water supply systems, emergency condition of a significant part of water supply and sewerage networks, etc. [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%